Review: Mesenchymal Stem Cell Therapy in Canine Osteoarthritis Research: “Experientia Docet” (Experience Will Teach Us) - Brondeel, Carlien; Pauwelyn, Glenn; de Bakker, Evelien; Saunders, Jimmy; Samoy, Yves; Spaas, Jan H. (Frontiers in Veterinary Science, 2021)
Osteoarthritis (OA) is currently an incurable and progressive condition in dogs causing chronic joint pain and possibly increasing disability. Due to the poor healing capacity of cartilage lesions that occur with OA, development of effective therapeutics is difficult. For this reason, current OA therapy is mostly limited to the management of pain and inflammation, but not directed ad disease modification. In the search for a safe and effective OA treatment, mesenchymal stem cells (MSCs) have been of great interest since these cells might be able to restore cartilage defects. The designs of OA studies on MSC usage, however, are not always consistent and complete, which limits a clear evaluation of MSC efficacy. The general study results show a tendency for to improve lameness, joint pain and range of motion in dogs suffering from naturally-occurring OA. Assessment of the cartilage surface demonstrated the ability of MSCs to promote cartilage-like tissue formation in artificially created cartilage defects. Immunomodulatory capacities of MSCs also seem to play an important role in reducing pain and inflammation in dogs. It should be mentioned, however, that in the current studies in literature there are specific design limitations and further research is warranted to confirm these findings.